Prospects for the Organization Expanded Surveillance System for Salmonella in Russia - S. H. Rozhnova; N. K. Akulova; O. A. Khristukhina (Эпидемиология и вакцинопрофилактика)
The results of development and implementation of a global Salmonella surveillance system performed by a reference center for the salmonellosis monitoring in a number of areas around Russia, which are the main bases of the center, are discussed in the paper. Given that the representatives of the three Salmonella serovars (S. Enteritidis, S. Typhimurium and S. Infantis) make up to 80% of all Salmonella isolates from various sources, it is advisable to exclude data on groups BCD salmonellosis from the form number 2 (Reports on infectious and parasitic diseases), replacing it with three major Salmonella serovars. It is reasonable to exclude information regarding serogroups. The conclusion is that within the global surveillance system it is necessary to promote interagency collaboration and communication of specialists in different fields. The forecast of epidemic situation for salmonellosis in the next few years is also generated.